Religious Guidance Strategy for Children in Conflict with the Law at the Antasena Rehabilitation Center, Magelang - Syafahira, Sarah; Mawardi, Imam; Subur (Universitas Muhammadiyah Yogyakarta, 2024)
Adolescence is a vital age period where difficulties can be encountered in life. Having an unstable psychological state can lead to the disruption of social functioning. Problems can occur during the learning and playing process, yet can also become extreme as far as committing crimes. The teenagers who commit crimes can be triggered due to a lack of understanding of their religion. The Antasena Rehabilitation Center provides social rehabilitation for children in conflict with the law, including religious guidance. To what extent do religious instructors provide guidance on faith, morals, and worship for ABHs who are naughty? This research uses descriptive qualitative research at the Antasena Rehabilitation Center and highlights the religious guidance used by religious instructors and the obstacles they face. The results of this study are expected to contribute to selecting the appropriate guidance strategies in the field of aqidah morals and worship for children who conflict with the law at the Antasena Rehabilitation Center in Magelang.